Selenium mass balance and flux in water of Pariette Wetlands, Utah (USA). (February 2020) - Jones, Colleen P.; Amacher, Michael C.; Grossl, Paul R.; Jacobson, Astrid R.
Abstract: Selenium (Se) has potentially deleterious impacts on flora and fauna of aquatic ecosystems. As Se moves through a wetlands system, various processes such as sorption onto sediments, plant uptake, and volatilization into the atmosphere can attenuate Se resulting in its storage in the wetlands. A comparison of inlet and outlet Se fluxes can be used to determine the mass of Se stored in a wetlands system. Inlet and outlet total Se concentrations and water discharge were measured at the Pariette Wetlands, UT, and used to calculate Se fluxes. The difference between inputs and outputs or fluxes gave great insight into how much Se was being retained or stored in the wetlands. The average influx of Se was 1530 kg year −1 and outflux was 380 kg year −1 . On average, 75% (1150 kg year −1 ) of Se entering the wetlands was retained or stored by some biogeochemical process. Processes associated with Se retention included bioaccumulation into the biota, volatilization by plants and sediments, precipitation of insoluble phases, and sorption to sediments, which accounted for most of the attenuated Se. Water movement through the Pariette Wetlands system did not appreciably alter annual Se attenuation rates. Input, output, storage, and fate of Se for four other wetlands were compared with Pariette Wetlands with Se storage being similar among three of the wetlands: Tulare Lake (65%), Imperial (46%), Brawley (72%), and Pariette (75%). Highlights: Retention of Se in an arid land wetland system was influenced mostly by hydrology and sorption to sediments. Bioaccumulation of Se by biota and subsequent volatilization were minor sources of partitioning for Se in this ecosystem. Pariette wetland provides valuable services of removal of bioavailable Se to this ecosystem and has comparable to storage of Se to other wetlands.